Rectal stricture in a bonnet monkey (Macaca radiata) : A case report (Journal of Laboratory Animal Science, 2024)
A six-year-old female bonnet monkey was noticed with a bloated abdomen seven days after experimentation. A plain  radiograph was taken to determine the cause of bloating. However, the plain radiograph did not reveal any significant  changes except patches of gas in the abdomen. Hence, a contrast radiograph was done with a barium meal. A constriction  was observed in the rectal region in contrast radiograph. An emergency laparotomy was done and stricture was surgically  corrected by an end-to-end anastomosis.
Keywords: Rectal strictures; ultrasonogram